Предмет: Алгебра, автор: aisulukubenbaeva

номер 6.14
помогите пожалуйста ​

Приложения:

Ответы

Автор ответа: сок111213
2

1)

 \frac{ {a}^{2} + 2ab +  {b}^{2}  }{ {a}^{2}  -  {b}^{2} }  =  \frac{(a + b) {}^{2} }{(a - b)(a + b)}  =  \frac{a + b}{a - b}

2)

 \frac{ {x}^{2} - 2x + 1 }{ {x}^{2}  - 1}  =  \frac{(x - 1) {}^{2} }{(x + 1)(x - 1)}  =  \frac{x - 1}{x + 1}

3)

 \frac{3 {a}^{2}  - 6ab + 3 {b}^{2} }{6 {a}^{2} - 6 {b}^{2}  }  =  \frac{3(a - b) {}^{2} }{6(a + b)(a - b)}  =  \frac{a - b}{2a + 2b}

4)

 \frac{5 {m}^{2} + 10mn + 5 {n}^{2}  }{ {15m}^{2} -  {15n}^{2}  }  =  \frac{5(m + n) {}^{2} }{15(m + n)(m - n)}  =  \\  \frac{m + n}{3m - 3n}

Похожие вопросы
Предмет: Математика, автор: vikam3766